UPAYA MENINGKATKAN ADMINISTRASI PERKAWINAN BELUM TERCATAT MELALUI PROGRAM KALIMASADA DI KELURAHAN RUNGKUT KIDUL - Nabila, Nabila (Department of Public Administration, Faculty of Social and Political Science, Universitas, 2024)
This research discusses the results and challenges of the Kalimasada Program (Community Awareness of Population Administration Area) implemented by the Department of Population and Civil Registration (Disdukcapil) of Surabaya City, focusing on the unregistered marital status services in Rungkut Kidul Sub-district. The program aims to increase community awareness about the importance of orderly and accurate population administration. The research method used is descriptive qualitative with primary data from observations, interviews, and documentation, as well as secondary data from journals, articles, and news media. Although the program achieved its target of 100 percent for unregistered marital status services in RW 001 to RW 006, some residents remain unassisted due to obstacles such as inaccurate data, difficulty in locating residents, and lack of understanding about the importance of population administration. Collaborative efforts between survey officers, RW/RT/KSH officials, and residents, as well as more intensive socialization, are needed to overcome these obstacles. With strong support, the Kalimasada Program is expected to create an orderly administrative environment, support community security and order, and facilitate residents' access to public services.